An Ergonomic Evaluation of Mosque Ablution Areas (Shadirvans): A User Perception Study - Iseri, Ali (Publisher Cv. Inara, 2026)
Mosque ablution areas (shadirvans) play a critical role in supporting ritual purification; however, their design is largely unstandardized and rarely evaluated from an ergonomic perspective. This study investigates the effectiveness of existing shadirvan designs by assessing user perceptions of comfort, safety, hygiene, and usability. A questionnaire-based survey was administered through structured interviews with 200 male users across 15 mosques in Istanbul, Türkiye. Fourteen Likert-scale items were used to evaluate key design and functional aspects of shadirvans. Descriptive analyses and multivariate analyses of variance (ANOVA) were conducted to examine the effects of demographic factors and mosque-specific design characteristics on user perceptions. The results indicate that while shadirvans are generally preferred over alternative ablution solutions, their performance is inconsistent and often insufficient. Common problems were identified in footwear management, water splashing control, and the organization of wet and dry zones. Traditional features such as shared clogs were largely perceived as uncomfortable and unhygienic. Statistical analyses revealed that user perceptions were predominantly influenced by the mosque itself, rather than by demographic characteristics, highlighting the strong impact of design variability. These findings provide empirical evidence that the absence of standardized design guidelines leads to significant differences in usability and user satisfaction. The study underscores the need for evidence-based, user-centered design standards to improve comfort, hygiene, and safety in mosque ablution facilities.